2009
DOI: 10.1145/1595061.1595064
|View full text |Cite
|
Sign up to set email alerts
|

Combating obesity trends in teenagers through persuasive mobile technology

Abstract: Throughout the last decade, there has been an alarming increase in obesity prevalence among adults and teens throughout the world. Obesity has been found to increase the risk of developing diabetes, cardiovascular diseases, and some cancers. Due to the many health risks associated with obesity, an increase in prevalence has also pressured health care systems and the finances of the individual. Our research proposes to decrease obesity prevalence in adults by motivating teens to become or continue being physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Cool has been described in terms of adjectives by many different commentators -some take a view of cool as being very much about consuming, others focus on cool as it applies to behaviours. Theories of the causes and motivations for cool also highlight the importance of the earning of social capital within cool subgroups through cultural subgroup emulation [2] and autonomy from mainstream society [3]. Our initial theory of cool is that it is different things in diminishing proportions within a hierarchy.…”
Section: Theorising About Cool Designmentioning
confidence: 99%
“…Cool has been described in terms of adjectives by many different commentators -some take a view of cool as being very much about consuming, others focus on cool as it applies to behaviours. Theories of the causes and motivations for cool also highlight the importance of the earning of social capital within cool subgroups through cultural subgroup emulation [2] and autonomy from mainstream society [3]. Our initial theory of cool is that it is different things in diminishing proportions within a hierarchy.…”
Section: Theorising About Cool Designmentioning
confidence: 99%
“…For example, marketing and phone companies might seek to access dispositional information about their customers to design customized offers and advertisements [4]. Appraising users dispositions through automatically collected data could also benefit the field of human-computer interface where personality has become an important factor [5]. Finally, finding ways to extract personality and, more broadly, psycho-social variables from countryscale datasets might lead to unprecedented discoveries in social sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Ethical considerations were neither implicitly nor explicitly mentioned in the studies by colleagues (2009, 2010) or by Arteaga and colleagues (Arteaga, Kudeki, & Woodworth, 2009;Arteaga et al, 2010), despite the latter working exclusively with teenagers. Consolvo et al (2006), Landay (2009), andConsolvo et al (2008) mentioned providing participant rewards, with the latter two also indicating use of consent forms in their studies.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…However, in most cases, the authors revealed only a description of what was used and not why the approaches were chosen or, necessarily, how the instruments were developed and applied. All but Ahtinen et al (2009) and Arteaga et al (2009Arteaga et al ( , 2010 used pedometers or accelerometers to capture participants' physical activity; these data were supplemented by participants' self-reported journal entries in the studies of Consolvo et al (2006Consolvo et al ( , 2008Consolvo et al ( , 2009) and King et al (2008). Ahtinen et al (2009) also used journals, but did not capture physical activity data.…”
Section: Techniques For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation